DAMPAK POLITIK KEBIJAKAN PERATURAN PEMERINTAH TERHADAP EKSISTENSI PESANTREN - Muhammad Abdulloh (Universitas Yudharta Pasuruan, 2019)
This research aims to discuss the dynamics of the existence of Pesantren on the policy of born governments. The relationship with the public policy of government Law number 55 year 2007. The presence of this policy as a government step in aligning the sustainability of the pesantren that must be noticed by the government in terms of its existence. This type of research is a qualitative dexskriptif and uses a phenomenological approach. The research of this primary purpose is to know how the political impact of government regulation number 55 year 2007 has been the existence of Pesantren. The results of this research show that the birth of PP number 55 year 2007 can be assumed to be part of the political product. In general, the relationship between education and politics is not merely a relationship affecting each other, but on the other hand is also a functional relationship. Institutions and educational processes run a number of significant political functions. Disislain with legalized PP number 55 year 2007 seems to give attention to the public that the government in terms of religious education is very concerned about the existence of Pesantren.